Islam in Tajikistan : actors, discourses, conflicts - Schmitz, Andrea (2015)
Zusammenfassung: The revival of Muslim values and ideas in Central Asia is perceived primarily through the lens of security, both among local regimes and by the West. The focus on extreme forms of Islam, however, prevents a balanced assessment of the religious discourse itself and obscures the reasons for the growing attraction of Islam and its potential as a force for order in the post-Soviet states. This study explores the social and political background to the revival of Islamic discourses, networks and practices in Tajikistan since the end of the Soviet Union, identifying the central actors, and laying out the intellectual and social coordinates of the symbolic struggles they are involved in. The growing significance of Islam as a source of moral and practical guidance is associated with a differentiation and pluralisation of the landscape of actors and discourses. The interpretative monopoly of the Hanafite clergy, who cultivate a tradition of tolerance towards culture-specific ritual practice and secular lifeworlds, is now challenged by reformist and universalist doctrines that reject the pragmatic consensus of the religious establishment. The state responds by suppressing the influence of religion through increasingly pervasive surveillance, but this cannot prevent the dissemination of the unwanted teachings. Reversing the tide would demand pro-active investment in good religious education. (SWP Research Paper)